UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN TEKS EKSPLANASI ILMIAH MELALUI PENDEKATAN SAINTIFIK BAGI SISWA KELAS VI SDN TANGKIL - Indah Nurahayu; Asep Samsudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
ABSTRACT This research was conducted in order to improve the ability to read and understand scientific explanatory texts through a scientific approach. This research was conducted at Tangkil Public Elementary School for the 2022-2023 school year. The subject of this research is class VI which consists of 24 students. The method used in this study is the class action research method (CAR). The data collection methods used are written tests, observational methods and data analysis by calculating the results of the students' learning ability test. Based on the analysis of the initial test results, the researcher found that 8 students (33.33%) of the 24 students were able to achieve the KKM that had been determined, namely 70, while the average score in the initial test was 60. The results of the first cycle test showed that the percentage of students who completed only 13 people (54.6%) and as many as 11 students (45.83%) did not get a complete score. In cycle II, the students who completed it increased significantly by 21 people (87.5%), and only 3 students who had not completed it (12.5%). After the final test was carried out, 23 students (95.83%) passed and only 1 person (4.16%) did not complete. From the increase in classical mastery obtained by students, it can be concluded that the scientific approach can improve the ability to read comprehension of class VI scientific explanation texts. ABSTRAK Peneliti melakukan penelitian bertujuan untuk meningkatkan kemampuan membaca pemahaman teks eksplanasi ilmiah melalui pendekatan saintifik. Penelitian ini dilaksanakan di SD Negeri Tangkil tahun ajaran 2022-2023. Subyek penelitian ini adalah kelas VI dengan jumlah siswa 24 orang. Metode yang digunakan dalam penelitian ini adalah metode penelitian tindakan kelas (PTK). Teknik untuk mengumpulkan data yang digunakan yaitu tes tertulis, observasi dan hasil analisis data dengan menghitung kemampuan belajar siswa. Berdasarkan hasil analisis pertama penelitian, peneliti menemukan bahwa 8 siswa (33,33%) dari 24 siswa dapat memperoleh KKM yang telah ditetapkan yaitu dengan nilai angka 70, sedangkan rata-rata kelas satu adalah 60. Hasil tes siklus pertama menunjukkan hanya 13 siswa (54,6%) yang lulus dan 11 siswa (45,83%) tidak mendapat nilai tuntas. Pada siklus kedua jumlah siswa yang tuntas secara signifikan sebanyak 21 orang (87,5%) dan hanya 3 siswa yang tidak tuntas (12,5%). Setelah ujian akhir, 23 siswa (95,83%) lulus dan hanya 1 orang (4,16%) yang tidak lulus. Dari peningkatan ketuntasan secara klasikal yang diperoleh siswa dapat disimpulkan bahwa pendekatan saintifik dapat meningkatkan kemampuan membaca pemahaman teks eksplanasi ilmiah kelas VI.